ANALISIS PERSEDIAAN BAHAN BAKU PRODUK USAHA SALE PISANG INDUSTRI RUMAH TANGGA âSOFIEâ DI KOTA PALU - AR. Mado, Fadlun (AGROTEKBIS, 2016)
This research aims to understand the number of reservations raw materials banana economically on industrial households sale banana in the city of Palu, to know the right time to reorderÂ  raw materials, and to know the cost of efficient in every time reservations. This study was conducted on industrial householdsÂ  âSofieâ in the city of Palu, the determination of location is deliberately (purposive). Research carried out in march until may 2014. The analysis used in this research was descriptive analysis and analysis Economic Order Quantity (EOQ). Â The analysis shows that by using the method EOQ the use of raw materials more economical than the use of raw materials uses the company, by using the method EOQ the number of buy raw materials more economical. The average number of the purchase of 245.88 kg, with the frequency of the reservations every month is twice. The total cost issued for supplies stock of Rp.987,566.24, the cost increased because the market demands increaed.